Pulmonary fibrosis in patients with COVID-19: A review - Alexander G. Chuchalin (Терапевтический архив, 2022)
The viral infectious disease pandemic caused by SARS-CoV-2 has affected over 500 million people and killed over 6 million. This is the official data provided by the WHO as of the end of May 2022. Among people who have recovered from COVID-19, post-COVID syndrome is quite common. Scattered epidemiological studies on post-COVID syndrome, however, indicate its high relevance. One of the manifestations of post-COVID syndrome is the development of pulmonary fibrosis (PF). This article is devoted to the analysis of literature data on epidemiology, immunomorphology, as well as X-ray morphological and functional characteristics of PF in patients with post-COVID syndrome. Attention is drawn to the various phenotypes of the post-COVID syndrome and the incidence of PF, which, as clinical practice shows, is most common in people who have had severe COVID-19. This article discusses in detail the molecular biological and immunological mechanisms of PF development. The fibrotic process of the lung parenchyma is not an early manifestation of the disease; as a rule, radiomorphological signs of this pathological process develop after four weeks from the onset of acute manifestations of a viral infection. The characteristic signs of PF include those that indicate the process of remodulation of the lung tissue: volumetric decrease in the lungs, cellular degeneration of the lung parenchyma, bronchiectasis and traction bronchiolectasis. The process of remodulating the lung tissue, in the process of fibrosis, is accompanied by a violation of the lung function; a particularly sensitive test of functional disorders is a decrease in the diffusion capacity of the lung tissue. Therefore, in the process of monitoring patients with post-COVID syndrome, a dynamic study of the ventilation function of the lungs is recommended. The main clinical manifestation of PF is dyspnea that occurs with minimal exertion. Shortness of breath also reflects another important aspect of fibrous remodulation of the lung parenchyma oxygen dissociation is disturbed, which reflects a violation of the gas exchange function of the lungs. There are no generally accepted treatments for PF in post-COVID syndrome. The literature considers such approaches as the possibility of prescribing antifibrotic therapy, hyaluronidase, and medical gases: thermal helium, nitric oxide, and atomic hydrogen. The article draws attention to the unresolved issues of post-covid PF in people who have had COVID-19.